Polygonal gold nanocrystal induced efficient phase transition in 2D-MoS2 for enhancing photo-electrocatalytic hydrogen generation - Das S.; Sharma U.; Mukherjee B.; Sasikala Devi A.A.; Velusamy J. (My University, 2025)
Plasmonic nanocrystals (NCs) assisted phase transition of two-dimensional molybdenum disulfide (2D-MoS2) unlashes numerous opportunities in the fields of energy harvesting via electrocatalysis and photoelectrocatalysis by enhancing electronic conductivity, increasing catalytic active sites, lowering Gibbs free energy for hydrogen adsorption and desorption, etc. Here, we report the synthesis of faceted gold pentagonal bi-pyramidal (Au-PBP) nanocrystals (NC) for efficient plasmon-induced phase transition (from 2 H to 1 T phase) in chemical vapor deposited 2D-MoS2. The as-developed Au-PBP NC with the increased number of corners and edges showed an enhanced multi-modal plasmonic effect under light irradiations. The overpotential of hydrogen evolution reaction (HER) was reduced by 61 mV, whereas the Tafel slope decreased by 23.7 mV/dec on photoexcitation of the Au-PBP@MoS2 hybrid catalyst. The enhanced performance can be attributed to the light-induced 2H to 1 T phase transition of 2D-MoS2, increased active sites, reduced Gibbs free energy, efficient charge separation, change in surface potential, and improved electrical conductivity of 2D-MoS2 film. From density functional theory (DFT) calculations, we obtain a significant change in the electronic properties of 2D-MoS2 (i.e. work function, surface chemical potential, and the density of states), which was primarily due to the plasmonic interactions and exchange-interactions between the Au-PBP nanocrystals and monolayer 2D-MoS2, thereby enhancing the phase transition and improving the surface properties. This work would lay out finding assorted routes to explore more complex nanocrystals-based multipolar plasmonic NC to escalate the HER activity of 2D-MoS2 and other 2D transition metal dichalcogenides. © 2023 IOP Publishing Ltd.